Electrical signal activity on upper limb muscle during mechanical load carrying : a study on emg-angle relationship - Tan, Yew Boon (2015)
The relationships between EMG and elbow angle were investigated to identify the signal on upper-limb muscle. Ten participants were their arm fixed in an isometric position and 100% of maximum voluntary contraction (MVC). Electromyogram (EMG) is the one kind of biological signal that can be recorded to evaluate the performance of skeletal muscles by means of a sensor electrode. Usually, an estimate of the EMG amplitude is obtained from the raw waveform recorded from the surface of the skin. Root Mean Square (RMS) and Maximum Absolute Value (MAV) have been calculated by using equation and raw waveform. Each participant of exerted force was recorded by using dynamometer. The result revealed that while the force decrease when elbow joint angle increase. This show that electrical signal on upper limb muscle getting stronger when angle of elbow joint increase and make force decrease